Copeland: I Never Sold a Single G-Pan: Recipient of TandT's Highest Award Reflects on PP Approach to Pan, Innovation - Loubon, Michelle (Sunday Guardian)
Attorney General of Trinidad and Tobago, Anand Ramlogan has accused G-Pan inventor Brian Copeland of selling steel pans for personal gain while the intellectual property rights are invested in the Government and proposed that Government take legal action against Copeland and three associates. Copeland argued that the real issue arose over the ownership of the PHI (Philamornic Harmonic Instrument).
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago; Musical inventions and patents; Intellectual property -- Trinidad and Tobago; Steel drum (Musical instrument) -- Patents